2018
DOI: 10.17521/cjpe.2018.0066
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the potential suitable habitat of <i>Impatiens hainanensis,</i> a limestone-endemic plant

Abstract: Aims Modelling potential distribution ranges of threatened species is of great significance for their conservation. In this paper, the distribution of potential suitable habitat of Impatiens hainanensis, a limestone-endemic and endangered plant in Hainan Island, was studied to provide scientific basis for their effective in situ conservation and re-introduction of I. hainanensis. Methods Based on eight occurrence sites and 12 environmental variables, the Maximum Entropy (MaxEnt) algorithm and GIS technology we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The leaves of I. hainanensis show morphological plasticity in response to changes in distribution habitat type. We hypothesized that, in addition to soil water and karst fissure water, horizontal precipitation may be an important source of water replenishment for I. hainanensis during the dry season: the plant canopy traps fog water, which drips and percolates into the karst fissure soil and is absorbed by the plant roots and leaves [39,40]. The functional traits of I. hainanensis leaves in response to changes in environmental factors along the altitude gradient can be considered a "water adaptation metamorphosis" under changes in the dominant water factor.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of I. hainanensis show morphological plasticity in response to changes in distribution habitat type. We hypothesized that, in addition to soil water and karst fissure water, horizontal precipitation may be an important source of water replenishment for I. hainanensis during the dry season: the plant canopy traps fog water, which drips and percolates into the karst fissure soil and is absorbed by the plant roots and leaves [39,40]. The functional traits of I. hainanensis leaves in response to changes in environmental factors along the altitude gradient can be considered a "water adaptation metamorphosis" under changes in the dominant water factor.…”
Section: Introductionmentioning
confidence: 99%
“…The research results of Hernandez et al (2006) andDeb et al (2017) both showed that in the case of few geographical locations (<10), even as low as 4 or 5, the MaxEnt model can still produce effective prediction results with high accuracy. At present, the model has been applied to simulate and predict the potential geographical distribution of endemic species (e.g., Impatiens hainanensis; Ning et al, 2020), national protected species (e.g., Phellodendron amurense; Huang et al, 2018), and many other key species.…”
Section: Introductionmentioning
confidence: 99%
“…The geographical distribution pattern of species and utilizing species distribution models (SDMs) to predict the potential geographical distribution of species are one of the hot research issues in the fields of biogeography and biodiversity conservation (Gaston, 2000 ; Ning et al., 2020 ; Tripathi et al., 2019a ; Zhang & Ma, 2008 ). Studying on the geographical distribution pattern and predicting the potential geographical distribution of species are of great significance for developing effective biodiversity conservation strategies (Lazo‐Cancino et al., 2020 ; Zhang et al., 2019 ), preventing and managing the spread of invasive alien species diffusion (Fernandes et al., 2019 ), and assessing the impact of climate change on species distribution (Lazo‐Cancino et al., 2020 ), and they are also an effective means of protecting and managing some rare and endangered species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological niche modeling has been increasingly used in species distribution, such as invasion species distribution, and species potential distribution under climate change ( Phillips et al., 2006 ; Huang et al., 2018 ; Ning et al., 2018 ). This model mainly uses known plant occurrence data and climate variables, according to specific algorithms, constructs a model, and projects the arithmetic consequence to predict the species’ current or potential distribution ( Phillips et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%